TRANSISI POLA PEMASARAN PERSPEKTIF PELAKU BISNIS AGROWISATA PADA MASA PEMULIHAN EKONOMI MASYARAKAT TEGALLALANG BALI - Purnama Sari, Desak Made Febri; Tiara Dewi, Ni Kadek Ajus; Oka Martini, Ida Ayu (Universitas Muhammadiyah Gresik, 2024)
The transition of the marketing pattern of agro-tourism business actors during the economic recovery of the Tegallalang community to Agro-tourism in the Tegallalang area aims to find out how the marketing patterns and strategies are carried out on agro-tourism in the Tegallalang during the endemic period. This research is descriptive qualitative with data analysis techniques using data reduction, data presentation, and drawing conclusions. The data collection method used in this study is by conducting observations, interviews, and documentation. The findings in this study showed no change in the marketing pattern carried out by agro-tourism business actors in the Tegallalang area where before the pandemic until the endemic period, agro-tourism in the Tegallalang still applied conventional and digital marketing patterns. At the point of marketing strategy, the findings obtained by researchers are more focused on online marketing strategies than conventional marketing strategies. In addition, this study shows a tendency for agro-tourism to choose social media Instagram, Facebook, Whatsapp, and Google maps as their marketing media. Another interesting finding found by conventional marketing researchers is they are still relatively used, this is evidenced by the agro- tourism business people who still apply word of mouth marketing through tour guides before the pandemic until now. In addition, the marketing strategy using the 4P marketing mix is still applied by agro-tourism business actors. Agro- tourism business actors in the Tegallalang area have also begun to implement other marketing strategies such as installing billboards, giving member cards, and giving business cards to each of their agro-tourism.